The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1961
DOI: 10.1139/z61-079
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Climate on Metabolic and Thermal Responses of Infant Caribou

Abstract: Metabolic and thermal responses of infant caribou to climate were measured during the June calving period on the barrens in the area of Mosquito Lake and Beverly Lake, N.W.T. It was found that temperature regulation was well established at birth and that the calves were very sensitive metabolically to cold, wind, and precipitation. The metabolic rate was doubled by a lowering of temperature to about 0 °C, but cold combined with wind and precipitation elevated the metabolic rate to over five times the resting v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1972
1972
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 2 publications
0
21
0
1
Order By: Relevance
“…Wet Svalbard reindeer calf fur appears more resistant to heat loss than other reindeer calf fur, and Svalbard reindeer are sedentary in behaviour (Tyler, 1987). Barren-ground caribou calves may move long distances in adverse weather (Hart et al, 1961), which results in metabolic costs for both movement and thermoregulation given the maximized surface area to volume ratio. In contrast, Svalbard reindeer calves remain on the calving sites, and whenever necessary may utilize the lying position, which reduces the surface area to volume ratio and hence exposure to wind, rain or temperature.…”
Section: Simulated Heavy Rainmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet Svalbard reindeer calf fur appears more resistant to heat loss than other reindeer calf fur, and Svalbard reindeer are sedentary in behaviour (Tyler, 1987). Barren-ground caribou calves may move long distances in adverse weather (Hart et al, 1961), which results in metabolic costs for both movement and thermoregulation given the maximized surface area to volume ratio. In contrast, Svalbard reindeer calves remain on the calving sites, and whenever necessary may utilize the lying position, which reduces the surface area to volume ratio and hence exposure to wind, rain or temperature.…”
Section: Simulated Heavy Rainmentioning
confidence: 99%
“…Hart et al (1961), studying infant caribou calves (Rangifer tarandus groenlandicus), observed that a combination of cold ambient temperatures, wind and wet fur increased the resting meta-7 Rain more important than windchill for insulation loss in Svalbard reindeer fur…”
Section: Introductionmentioning
confidence: 99%
“…However, of course, wetting of the pelt and wind may create a situation which is barely tolerated by infants (see e.g. Hart et al 1961). According to our data it is likely that shivering plays only a minor role in the heat production of a newly born calf.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of air velocity, direction and wetness of the skin on heat loss were examined as well. Hart et al (1961) studied the metabolic and thermal responses of infant caribou. The metabolic rate was doubled by a lowering of temperature to 0°C, but cold combined with wind and precipitation was observed to elevate the metabolic rate to over 5 times the resting value at 20°C.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of thermoregulatory ability in neonates is dependent upon such factors as body size, thermal insulation, degree of neuro logical control and thermogenic capability at birth (Hull, 1973)-Large neonates, such as newborn lambs, have thermorsgu'iatory abiiiiies quite simi'iar to adults (Âlaxander, 1361, 1362aAlaxandsr and Williams, 1962), and are able to maintain homeocherrriy when subjected to ambient temperatures as low as -10 C. Newborn caribou, due to tneir large size and weii-deveioped thermal insulation, thermoregusate with no apparent difficulty and are In thermal danger in the arctic only under wet, windy conditions (Lentz and Hart, 1960;Hart et al, 1961).…”
Section: Thermoregulation In Neonatesmentioning
confidence: 99%